HUBUNGAN ANTARA PERSEPSI SISWA TENTANG GAYA KEPEMIMPINAN TRANSAKSIONAL GURU DENGAN MOTIVASI BELAJAR BIOLOGI SISWA - Supriyatin, S; Miarsyah, Mieke; Melia, M (Universitas Negeri Jakarta, 2017)
The purpose of this study was to determined the correlation between students' perception of teacher transactional leadership style with Student motivation of study biology. Students have perception of teacher transactional leadership style during the learning process. Student perception about teacher transactional leadership style can be one of the factors that influence the motivation to learn biology. This perception may occur at each school included in SMA Negeri 31 Jakarta. This research was conducted in SMAN 31 Jakarta in May 2016. The method used was descriptive method through correlational studies with survey techniques. The total sample in this study were 85 students with simple random sampling technique. Having tested the research data were normally distributed and homogeneous. The regression equation Å¶ = 37,453+ 0.485X obtained. The correlation coefficient of 0.496.Which means that 21.9% of the variable motivation of study biology can be determined by the variable student perception about teacher transactional leadership style.